2014
DOI: 10.1177/1553350614528383
|View full text |Cite
|
Sign up to set email alerts
|

Ex Vivo Normothermic Machine Perfusion Is Safe, Simple, and Reliable

Abstract: Our study shows that NMP is safe, reliable, and provides superior graft preservation compared to CS in our DCD porcine model.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
74
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(74 citation statements)
references
References 20 publications
0
74
0
Order By: Relevance
“…In the past, we and others have demonstrated that warm perfusion (subnormothermic or normothermic) on its own improves liver grafts during the preservation period. In 2014, we demonstrated in a donation after circulatory death (DCD) pig LT model that warm perfusion improves the preservation of ECs and reduces bile duct injury .…”
Section: Discussionmentioning
confidence: 97%
“…In the past, we and others have demonstrated that warm perfusion (subnormothermic or normothermic) on its own improves liver grafts during the preservation period. In 2014, we demonstrated in a donation after circulatory death (DCD) pig LT model that warm perfusion improves the preservation of ECs and reduces bile duct injury .…”
Section: Discussionmentioning
confidence: 97%
“…All livers were flushed with 1 L of normal saline at 21°C through hepatic artery (HA) and portal vein (PV) cannulations to remove histidine tryptophan ketoglutarate solution or University of Wisconsin solution. All livers underwent 24 hours of NMP using the perfusion system previously reported . The perfusion system consisted of an organ receptacle, centrifugal pump, roller pump, oxygenator, and heat exchanger.…”
Section: Methodsmentioning
confidence: 99%
“…Although graft viability can be assessed in all machine perfusion setups, NMP theoretically offers the best context to sample the perfusate for injury markers (for example, ALT, lactate), since liver metabolism is maintained at a physiological level and additional injury by warm reperfusion is avoided. In a pig model of liver preservation, 10 h of NMP proved superior to SCS, as determined by liver injury parameters (AST release, bile production) as well as liver histology after 24 h of reperfusion (89). In a similar experimental model, SCS elicited severe biliary necrosis, compared with only mild biliary damage after NMP (90).…”
Section: Clinical Status Quo Of Organ Cooling In Liver Surgery Liver mentioning
confidence: 81%